Physical activity and quality of life in children: Findings from the Health Oriented Pedagogical Project (HOPP) - Rein Magnus Jensen; Asgeir Mamen; Christoffer Wang; Per Morten Fredriksen (PLoS ONE, 2026)
Purpose The purpose of this study was to examine the associations between a 5-year school-based physical activity (PA) intervention and quality of life (QoL) in children aged 6–12 years. Methods Data were collected through the Health Oriented Pedagogical Project (HOPP), a longitudinal study conducted in Norway. HOPP involved children and their parents from nine elementary schools (n = 2,140 children and 1,639 parents completed the QoL-questionnaire). Seven schools received the intervention (an additional 225 minutes of physical activity per week), while two schools served as controls following the standard curriculum. QoL was measured using the Inventory of Life Quality in Children and Adolescents (ILC), and physical activity (PA) was assessed using accelerometers. Covariates included father’s education level as a proxy for socioeconomic status (SES) and children’s waist-to-height ratio (WHtR). Results The analysis revealed a significant positive association between MVPA and QoL (β = 0.008, p < 0.001), although the effect size was small. SES was significantly associated with QoL in intervention schools (β = 0.249, p < 0.001), while WHtR was negatively associated with QoL in both groups, with a stronger association in control schools (β = −4.344, p = 0.010). The control schools exhibited higher QoL scores than the intervention schools, with an average 0.5-point advantage (β = 0.458, p < 0.001), likely reflecting underlying SES differences. Conclusion This study highlights the complex interplay between MVPA, SES, WHtR, and QoL in children. While MVPA was associated with better QoL, these associations varied according to factors such as age, SES, and WHtR, with no significant association observed for sex. The findings suggest that sustained and varied physical engagement in school settings may be relevant for children’s QoL. Moreover, school-based initiatives should consider multiple individual and environmental factors, particularly SES and physical health metrics, when interpreting or targeting QoL-related outcomes. Trial registration The study is registered at ClinicalTrials.gov (Identifier: NCT02495714). The trial was retrospectively registered on June 20, 2015. Baseline data collection was initiated in mid-January 2015.